Penerapan Model PBL Untuk Meningkatkan Hasil Belajar Siswa Pada Pokok Bahasan Gerak Makhluk Hidup di Kelas IX SMP Dian Todahe - Kesia Dadi; Jantje Ngangi; Dany Christian Posumah (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
This research was conducted in class IX of Dian Todahe Middle School for the 2021/2022 academic year, with 25 students as subjects. This research aims to improve student learning outcomes by applying the Problem-Based Learning (PBL) approach to learning the movement of living creatures. This particular form of research is included in classroom action research (CAR) classification. This research examines student learning outcomes by analyzing their test scores before and after their involvement in the learning process, with a particular focus on Biology education, which is related to the movement of living things. Research findings show an increase in student performance during cycle II, which is then accompanied by an increase in student engagement. Of the total number of students, 22 (88%) completed their studies by getting a maximum score of 65. On the other hand, three students (12%) could only complete their studies if they scored below 65. The learning outcomes achieved in cycle II have fulfilled the requirements for completion. Traditionally, there has been a visible improvement in students' understanding of the subject matter.